Old Shoes in a New Perspective—Fashioning Archaeology. (4th May 2017) - Andersen, Vivi Lena
Abstract: The article addresses the challenge of combining the very diverse fields of archaeology and fashion. The Museum of Copenhagen has carried out a number of major archaeological excavations that have contributed substantially to the museum's footwear collection, now consisting of approximately 6500 shoes and shoe parts. An ongoing PhD project aims to investigate aspects that affected Copenhageners' footwear in the period 1200–1800 AD, and to explore the relationship between craft and the functional and fashion-related aspects of how footwear developed, was designed and worn. The shoes themselves, written and iconographic sources, natural sciences and experimental collaborations with modern-day shoemakers and foot specialists shed new light on our understanding of footwear history. Footwear was originally invented to protect feet against natural and climatic conditions, but it also became an indicator of how we want to be seen by others—with fashion seemingly being a crucial aspect of how and why footwear developed the way it did. In the analysis of the choice and need dichotomy there are interesting approaches in the theory of human ‒ thing entanglement and engaging archaeologically with the fashion phenomenon that can bring new perspectives on past, present and future.